Accurate electronic properties and non-linear optical response of two-dimensional MA2Z4. Issue 10 (9th March 2021) - Yang, Jia-Shu; Zhao, Luneng; LI, Shi-Qi; Liu, Hongsheng; Wang, Lu; Chen, Maodu; Gao, Junfeng; Zhao, Jijun
Abstract : The band gap/work function difference between PBE and HSE06 is 26%–101%/4%–18%, implying HSE06 level calculation is highly required. The photon energy-dependent second-order non-linear coefficients indicate extraordinary SHG response from MA2 Z4 . Abstract : Two-dimensional MA2 Z4 (M = Mo, W, V, Nb, Ta, Ti, Zr, Hf, or Cr; A = Si or Ge; Z = N, P, or As) is a new lead in the 2D family, because it exhibits versatile properties by tuning the components M, A and Z . However, theoretical studies on MA2 Z4 are quite limited, and electronic properties are mainly studied by standard DFT levels, which seriously underestimates the band gap. Here, we systematically investigated the electronic properties and nonlinear optical response of MA2 Z4 using a hybrid HSE06 functional. It was found that replacing component Z changes the lattice constant most, while the lattice influence by component M substitution is only slight. We showed that the gap difference between PBE and HSE06 is generally about 30% but can be up to 101%. (M IV = Hf, Ti, or Zr)Si2 N4 possesses multi-valley characteristics. Furthermore, the second-harmonic generation (SHG) responses of various MA2 Z4 composites were also calculated. Three non-zero elements of second order non-linear susceptibilities are revealed for MA2 Z4 with the relationship: d 16 = d 21 = d 22, indicating that MA2 Z4 belongs to the D 3 H 1 space group. HfSi2 N4 possesses a multi-valley characteristic, and exhibits the largest susceptibility under broad wavelengths and the value of d 21 reaches 3697.04 pm V −1 at band gap resonance energy. Intriguingly, the non-linear coefficients of MoSi2 P4 and MoSi2 As4 in the IR region are two orders of magnitude larger than those of other well-known non-linear crystals, such as LiGaS2 and BaAl4 S7 . We further explored the anisotropic SHG response by the polar plot of intensity under different incident light into MA2 Z4 . Our work provides theoretical guidelines for further experimental explorations of MA2 Z4 and paves the way for its utilization in non-linear optic devices.